FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN PERUBAHAN FISIK PADA IBU PREMENOPAUSE - Sari Ida Miharti; Meli Prenti Ayu (Universitas Fort de Kock Bukittinggi, 2022)
(WHO) in 2020, the number of premenopausal women in Asia reaches 654 million people and in 2025 it is estimated to reach 1.2 billion with an average age of 40-50 years. In Indonesia, the number of premenopausal women aged 40-50 years is 17.21 million and it is estimated that in 2035 it will reach 20.36 million. This study aims to determine the factors associated with anxiety physical changes in premenopausal women. The type of research used is analytic with a cross sectional study design conducted in the Work Area of the Lubuk Gadang Health Center. The population of all premenopausal women aged 40-50 who have a partner is 205 people with a simple random sampling technique of 67 people. The results of univariate analysis showed that 52.2% of premenopausal women did not receive support from their husbands. 46.3% have low knowledge, 43.3% have low economics, 25.4% have culture, and 41.8% experience moderate anxiety in physical changes. The results of statistical tests showed that there was a relationship between husband's support (p = 0.012 OR = 7.333), knowledge (p = 0.024 OR = 3.6), economics (p = 0.007 OR = 4.582), and culture (p = 0.002 OR = 7.583) with anxiety about physical changes. It can be concluded that there is a relationship between husband's support, knowledge, economy, and culture with anxiety about physical changes. For this reason, it is recommended for health workers, especially midwives, to provide counseling about reproductive health, especially about the changes that occur during the premenopause period to increase mothers' understanding of how to deal with menopause and reduce complaints before menopause. It is also recommended for mothers to do Kegel exercises and husbands to provide motivation and support in undergoing the premenopausal period. Keywords: Husband's Support, Knowledge, Economy, Culture, Anxiety